Improved ICU design reduces acquisition of antibiotic-resistant bacteria: a quasi-experimental observational study - Levin, Phillip D (BioMed Central, 2011)
INTRODUCTION: The role of ICU design and particularly single-patient rooms in decreasing bacterial transmission between ICU patients has been debated. A recent change in our ICU allowed further investigation. METHODS: Pre-move ICU-A and pre-move ICU-B were open-plan units. In March 2007, ICU-A moved to single-patient rooms (post-move ICU-A). ICU-B remained unchanged (post-move ICU-B). The same physicians cover both ICUs. Cultures of specified resistant organisms in surveillance or clinical cultures from consecutive patients staying >48 hours were compared for the different ICUs and periods to assess the effect of ICU design on acquisition of resistant organisms. RESULTS: Data were collected for 62, 62, 44 and 39 patients from pre-move ICU-A, post-move ICU-A, pre-move ICU-B and post-move ICU-B, respectively. Fewer post-move ICU-A patients acquired resistant organisms (3/62, 5%) compared with post-move ICU-B patients (7/39, 18%; P = 0.043, P = 0.011 using survival analysis) or pre-move ICU-A patients (14/62, 23%; P = 0.004, P = 0.012 on survival analysis). Only the admission period was significant for acquisition of resistant organisms comparing pre-move ICU-A with post-move ICU-A (hazard ratio = 5.18, 95% confidence interval = 1.03 to 16.06; P = 0.025). More antibiotic-free days were recorded in post-move ICU-A (median = 3, interquartile range = 0 to 5) versus post-move ICU-B (median = 0, interquartile range = 0 to 4; P = 0.070) or pre-move ICU-A (median = 0, interquartile range = 0 to 4; P = 0.017). Adequate hand hygiene was observed on 140/242 (58%) occasions in post-move ICU-A versus 23/66 (35%) occasions in post-move ICU-B (P < 0.001). CONCLUSIONS: Improved ICU design, and particularly use of single-patient rooms, decreases acquisition of resistant bacteria and antibiotic use. This observation should be considered in future ICU design.